The Effect of Administrative Ethics on Service Quality - Latif, Abdul (Journal Social Civilecial, 2023)
The study's objective is to glean participants' perspectives on administrative ethics' effect on service quality. This research combined quantitative and associative approaches. The technique used is called "saturated sampling," and it requires determining whether or not the sample can include every member of the community. The information utilized in this analysis was gathered using a combination of in-person interviews, online surveys, and direct observation. Simple linear regression analysis was employed to examine the data, and SPSS 24.0 was the software of choice for this task. Results from a test of the hypothsesis that "administrative ethics (X) has a positive influence on service quality" are consistent with the research's result that ethics in administration has a positive effect on service quality (Y). This can be seen by comparing the values of tcount and ttable; tcount is greater by 10,696.